2017
DOI: 10.1073/pnas.1620843114
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum erythrocyte-binding antigen 175 triggers a biophysical change in the red blood cell that facilitates invasion

Abstract: Invasion of the red blood cell (RBC) by the Plasmodium parasite defines the start of malaria disease pathogenesis. To date, experimental investigations into invasion have focused predominantly on the role of parasite adhesins or signaling pathways and the identity of binding receptors on the red cell surface. A potential role for signaling pathways within the erythrocyte, which might alter red cell biophysical properties to facilitate invasion, has largely been ignored. The parasite erythrocyte-binding antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 59 publications
5
81
0
2
Order By: Relevance
“…Thus, in an attempt to increase erythrocyte cholesterol content, red cells were incubated with MβCD coupled cholesterol. As expected, a highly significant increase in erythrocyte bending modulus was observed, whilst no significant increase in membrane tension (a measure of cytoskeletal effects (Koch, et al 2017) was found at this concentration ( Fig 1E-F). To confirm that additional cholesterol had been incorporated into the cell membranes, cells were washed, lipid membrane extracted, purified, dried and resolubilised to measure cholesterol content.…”
Section: Artificial Incorporation Of Membrane Cholesterol Inhibits Psupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, in an attempt to increase erythrocyte cholesterol content, red cells were incubated with MβCD coupled cholesterol. As expected, a highly significant increase in erythrocyte bending modulus was observed, whilst no significant increase in membrane tension (a measure of cytoskeletal effects (Koch, et al 2017) was found at this concentration ( Fig 1E-F). To confirm that additional cholesterol had been incorporated into the cell membranes, cells were washed, lipid membrane extracted, purified, dried and resolubilised to measure cholesterol content.…”
Section: Artificial Incorporation Of Membrane Cholesterol Inhibits Psupporting
confidence: 81%
“…Based on our previous findings demonstrating that a reduction in the erythrocyte bending modulus resulted in an increased merozoite invasion efficiency (Koch, et al 2017), we hypothesised that stiffening the erythrocyte membrane by increasing cholesterol content would result in a lower merozoite invasion efficiency. Erythrocytes were incubated in media supplemented with a range of cholesterol concentrations, however, no change in the red cell bending modulus was found ( Fig 1A-D).…”
Section: Artificial Incorporation Of Membrane Cholesterol Inhibits Pmentioning
confidence: 98%
See 1 more Smart Citation
“…This can be useful in blood analysis, since RBC deformability might be altered in many blood related diseases and disorders, such as malaria, sickle-cell anemia, diabetes, etc. (13,14,21).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in elastic properties and shape of RBCs are of great interest in microcirculation research, because they affect many essential microvascular processes, including blood flow resistance (3)(4)(5), the viscosity of whole blood (6)(7)(8)(9), ATP release and oxygen delivery (10)(11)(12). Alterations in RBC material properties and shape are often associated with different blood diseases and disorders (13,14), such as sickle cell anemia (15,16), diabetes mellitus (17,18), and malaria (19)(20)(21). The importance of RBC behavior in flow also motivates large research efforts in blood processing and analysis using microfluidic devices (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%